Fraud and Corruption Prevention in Financial Reporting to Enhance National Attitudes and Nationalism - Fangela Myas Sari; Muhamad Ridho; Nisa Tiana; Esthe Daniela (Business, Accounting, and Knowledge Journal, 2026)
The increasing number of corruption cases in public institutions and state-owned enterprises (SOEs) such as PT Timah Tbk, PT Pertamina, and PT Asabri (Persero) indicates weaknesses in internal control systems and a decline in the moral integrity of public officials. This study employs the Fraud Triangle theory, which consists of pressure, opportunity, and rationalization, to identify the dominant factors contributing to fraudulent practices and their implications for national values. The findings reveal that opportunity is the most influential element driving fraud and corruption, followed by organizational pressure and moral rationalization by the perpetrators. Weak supervisory quality, transactional political culture, and the declining sense of nationalism are identified as key factors that intensify the potential for such misconduct.